The Volume Model of Tree Species Group in Peat Swamp Forest at Logging Concession Area of Tingang Karya Mandiri, Central Kalimantan - Qirom, Muhammad Abdul Qirom; Acep, Acep Akbar (Jurnal Wasian, 2020)
Tropical peat swamp forest (PSF) has a high species diversity and value including timber value. The valuation of timber is approached by calculating the stand volume. However, the volume model at PSF is not available for every species and species groups in specific site. This study aims to obtain a volume estimation model of species groups of tree species in peat swamp forest in Central Kalimantan. The model development and validation used 120 sample trees of the dipterocarpaceae and non-dipterocarpacae species. The distribution of sample trees is 70 % for the development model and 30 % for the validation stage. Modeling used linear and non-linear models). The selection of the best model used several criteria including: coefficient of determination, relative deviation (SR
Keywords: accuracy; timber; non-linear; validation